SENI PAHAT DALAM BALUTAN BATU ALAM SCULPTING ARTS IN NATURAL STONE (Science and Technology (SciTech), 2023)
Natural stone crafts are the work of artisans from Sleman Yogyakarta Regency which is the result of the development of the contemplation of previous products made of wood, metal, leather and rattan which are currently limited. This natural stone craft is made from local stone materials in Gunungkidul obtained by mining on the location of the residents' private land or village-specific land that has been permitted by the local government with the target of being able to increase selling power and the economy so that welfare increases. This research aims to raise white stone craftsmen to be better known through exhibitions and increase production through documenting products that have been made to develop the quality of their designs and then offer them through an export sub-bayer. So that the target one year later artisans are able to export directly. To obtain quality scientific data, the following research methods were used, namely qualitative research with a research population on the Chindelaras Creation Stones object at Kranggan I rt.01, rw.27, Jogotirto, Berbah, Sleman, Yogyakarta. The qualitative method is divided into three stages, namely the pre-field stage, the field work stage and the data analysis stage (Moleong, 2019: 127). The data obtained from the artisans will be documented and conveyed truthfully, so that research can be justified for the truth.